Role of memantine in adult migraine: a systematic review and network meta-analysis to compare memantine with existing migraine preventive medications - Li, Guanglu; Qu, Baoquan; Zheng, Tao; Duan, Shaojie; Liu, Lei; Liu, Zunjing (Frontiers in Pharmacology, 2024)
BackgroundWhile memantine has been considered a promising drug for migraine prevention, no conclusive evidence exists comparing its efficacy with other migraine-preventive medications. This network meta-analysis (NMA) aimed to access the effectiveness and acceptability of memantine and other guideline-recommended prophylactic agents for migraine.MethodsWe searched the Cochrane Register of Controlled Trials, Embase, PubMed, and ClinicalTrials databases from their inception to 1 June 2024. Randomized placebo-controlled trials (RCTs) examining the pharmacological prevention of adult migraine patients were included. The primary efficacy outcome was the change in migraine days, and the primary safety outcome was withdrawal due to adverse events. Secondary outcomes included 50% response rates and frequency of any adverse events. The analysis followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines.ResultsThirty-eight RCTs, including a total of 13,223 participants, were analyzed. Our analysis showed that memantine demonstrated the second-largest reduction in migraine days [standardized mean difference (SMD): −0.83; 95% confidence interval (CI): −1.26, −0.41 compared with placebo] and the highest 50% response rates [odds ratio (OR): 5.58, 95% CI: 1.31 to 23.69] in all studied interventions. Moreover, among all interventions, memantine appeared to show the lowest dropout rate and moderate frequency of adverse events. However, its confidence intervals contained null values.ConclusionThis study provides prioritisation evidence for memantine in migraine prevention, as memantine can significantly decrease the frequency of migraine attacks, improves response rates, and fair acceptability. These beneficial effects were not inferior to currently recommended pharmacological regimens. However, due to the lack of long-term efficacy and safety data, as well as few direct comparisons with active control agents, the estimates of memantine may be overly optimistic. Clinicians should interpret the findings of current NMA cautiously and apply them in a relatively conservative manner.